Place as overlap between the interests of regional geography and marketing - Matlovičová, Kvetoslava (Journal for Geography, 2007)
The new challenges presented by a place have launched a marketing research initiative that integrates various marketing approaches requiring not only a wide variety of knowledge in humanities, social sciences, and business disciplines, but also comprehension of the entire complexity of its product – a place. The intricacy of its very essence and nature has probably been one of the reasons why no consensus exists so far on how to define the marketing of place. Here is the space for geography to which a place represents an object of research, and to which a place is also part of the method of how to perform such research. This paper is dedicated to discussion about the issues of applicability of the concept of place in territorial marketing that forms the contact zone between regional geography and marketing.